(Un)doing Markets: Inter-Field Dynamics, Collective Action and the Emergence of Music Streaming - Yngfalk, Carl; Fyrberg Yngfalk, Anna; Skålén, Per (Sage publications, 2026)
This article examines field-level processes that condition actors’ efforts to mobilize collective strategic action for institutional change in markets, showing how such efforts may unsettle existing arrangements while simultaneously laying the groundwork for new ones. Drawing on strategic action field theory, we analyze the transformation of the recorded music market from physical records to online streaming in the early 2000s. Conceptualizing markets as configurations of interconnected fields, we develop a process model of inter-field dynamics demonstrating how exogenous shocks in proximate fields reconfigure power relations and enable coordinated action. Our analysis traces how collective mobilization destabilized incumbent structures, how struggles over legitimacy facilitated organizational appropriation of emerging practices, and how temporary settlements consolidated a new market infrastructure. We contribute to macromarketing theory by specifying the mechanisms through which market-shaping unfolds across interconnected fields and by explaining why disruption often culminates in settlements that re-stabilize, rather than displace, incumbent power.
Keywords: market-shaping; inter-ﬁeld dynamics; institutional change; collective action; power; strategic action ﬁelds; fi=Markkinointi|en=Marketing|